Cellulose nanofibers produced from various agricultural residues and their reinforcement effects in polymer nanocomposites. Issue 21 (18th February 2018) - Sinclair, Alexander; Jiang, Long; Bajwa, Dilpreet; Bajwa, Sreekala; Tangpong, Siwakorn; Wang, Xinnan
ABSTRACT: Cellulose nanofibers (CNFs) have gained widespread attention due to their extraordinary potential as superior reinforcement to improve physical and mechanical properties of polymer matrix nanocomposites. Biomass residues from local North Dakota represent a potential source for these high value structural constituents. Two types of soybean hull, wheat straw, and softwood flour were subjected to chemical pretreatments followed by mechanical fibrillation to produce CNFs. Atomic force microscopy and scanning electron microscopy results show that nanofibers with uniform diameters in the nanometer range can be easily synthesized. The nanofibers reinforcement potential was then explored via integration of the fibers into a poly(ethylene oxide) polymer matrix. Significant reinforcement effect of the nanofibers was observed from the nanocomposites: tensile modulus and yield strength of the nanocomposites were increased up to 154% and 103%, respectively. The CNFs extracted from the two types of soybean hull and wood flour showed stronger reinforcement (in terms of both modulus and yield strength) than that of the traditional wood pulp based CNFs. The nanofibers extracted from wheat straw showed higher strength but lower modulus compared with those of the traditional CNFs. More work is however needed to improve production reliability/repeatability of the agricultural residue based nanofibers. © 2018 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2018, 135, 46304. Abstract :